2010
DOI: 10.1016/j.jss.2009.11.244
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Intestinal Alkaline Phosphatase in the Maintenance of Local Gut Immunity

Abstract: Background and Aims-Intestinal alkaline phosphatase (IAP) is a gut mucosal defense factor known to dephosphorylate lipopolysaccharide (LPS); however, the role of IAP in the gut response to luminal bacteria remains poorly defined. We investigated immune responses of wild-type (WT) and IAP-knockout (IAP-KO) mice to LPS and Salmonella typhimurium challenges. Methods-Cryostat sectioning and standard indirect immunohistochemical staining for major histocompatibility complex (MHC) class II molecules were performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…In the present study we provide evidence that the brush-border enzyme IAP promotes the growth of commensal bacteria. IAP exerts a number of beneficial effects on the gut, including the maintenance of local gut immunity (8), enhancing barrier function, reducing excessive inflammation, and inhibiting metabolic endotoxemia (4,12,14,21,26). The present study delineates another key beneficial impact of the IAP enzyme, promoting the growth of the commensal flora.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study we provide evidence that the brush-border enzyme IAP promotes the growth of commensal bacteria. IAP exerts a number of beneficial effects on the gut, including the maintenance of local gut immunity (8), enhancing barrier function, reducing excessive inflammation, and inhibiting metabolic endotoxemia (4,12,14,21,26). The present study delineates another key beneficial impact of the IAP enzyme, promoting the growth of the commensal flora.…”
Section: Discussionmentioning
confidence: 68%
“…Much recent progress has been in made in delineating the physiological and pharmacological properties of the IAP enzyme. IAP has the ability to dephosphorylate a variety of bacterial and hostderived ligands (LPS, CpG DNA, flagellin, UDP), each of which works through a specific receptor to exert its inflammatory impact on target cells (8,39). Here we show that IAP reverses the growth-inhibitory effects of various nucleotide triphosphates, indicating that these nucleotides are also IAP targets (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of IAP in detoxifying LPS and reducing the inflammatory response has been investigated (Koyama et al, 2002;Bates et al, 2007;Bol-Schoenmakers et al, 2010;Chen et al, 2011). It has been demonstrated that early weaning of piglets reduces the expression of IAP mRNA, and may predispose animals to enteric infections and diarrhea events, resulting in poor health and impaired growth (Lackeyram et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that IAP expressed on apical surfaces of microvillus membranes of enterocytes detoxifies LPS in the intestine, thereby preventing inflammation, sustaining barrier function, and maintaining homeostasis within intestinal flora [501][502][503][504]. This hypothesis is supported by the analysis of IAP knockout mice [505,506]. In addition, LPS-dephosphorylating activity of gut-derived IAP has been suggested to be part of the endogenous hepatocyte defense system against LPS [507].…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 95%